The WTO and agriculture - Anderson, Kym; Josling, Tim (Cheltenham, UK ; Northampton, MA, USA : Edward Elgar Pub., 2005)
Examines: Why agricultural markets have been noted for relatively high degrees of government intervention and in particular for rising levels of protection? How was agricultural trade treated in the GATT and WTO? What opportunities are on the horizon? and other issues.
Includes bibliographical references and index.
oif 20/07/16
Loans
Keywords: Produce trade; Agriculture